Exploring the impact of the digital economy on green total factor productivity in China: A spatial econometric perspective - Sun, Xin; Jiang, Ke; Cui, Zhikun; Xu, Jilan; Zhao, Xin (Frontiers in Environmental Science, 2023)
The digital economy is considered a driving force of green economic development. However, only a few studies have examined the relationship between the digital economy and green total factor productivity (GTFP). According to the principal component method and super-efficient Slacks-based measure model, the digital economy level and green total factor productivity GTFP were measured for China’s provinces based on panel data from 2013 to 2019. The spatial econometric model was then used to analyze the effects of the digital economy level on green total factor productivity GTFP. Results showed that the overall level of green total factor productivity GTFP maintained a steady growth trend, with an average yearly growth of 4.19%. Significant regional differences reflecting the development characteristics of eastern, central, and western regions were also observed. Most provinces showed either high or low values of both green total factor productivity GTFP and digital economic development thereby revealing spatial heterogeneity for the different provinces and cities. The spatial Durbin model showed that the digital economy had a significant direct effect (0.1498) and spatial spillover effect (0.3438) on green total factor productivity GTFP, the latter being greater than the former, with this conclusion supported by the robustness test. Technological innovation positively regulates the contribution of the region’s digital economy to green total factor productivity GTFP and negatively regulates the spatial spillover of the digital economy to green total factor productivity GTFP in neighboring regions.